Cálculo dos coeficientes de conversão de dose equivalente e dose efetiva em termos do kerma no ar para fótons utilizando simulador - Cavalcante, Fernanda Rocha (2013)
Dosimetric quantities are necessary for evaluate the human exposures to radiation quantitatively and to describe relationships between the dose and biological effects caused by the interaction of radiation with the organs and tissues, providing a basis for estimating risks in radiological protection. Anthropomorphic simulators are threedimensional representations of the human body and coupled to a radiation transport code provides conversion coefficients for estimating the equivalent and effective doses through physical quantities, such as air kerma (Kair). In most published papers the exposure scenarios consist of simulators implemented in the standing posture. In this work we developed exposure scenarios in the Visual Monte Carlo (VMC) code using a female adult voxel simulator in standing and sitting postures. The simulator was irradiated by a plane source of monoenergetic photons with energy from 10 keV to 2 MeV in the antero-posterior (AP), postero-anterior (PA), right lateral (RLAT) and left lateral (LLAT) irradiation geometries. The conversion coefficients for equivalent and effective doses in terms of air kerma (H/Kair and E/Kair) were calculated for both scenarios and compared. The results show that the relative difference of conversion coefficients for the organs of the head and thorax was not significant (less than 5%) since the anatomic position of the organs is the same in both postures. The relative difference is more significant for organs of abdominal region, such as the ovaries (71% for photon energy of 20 keV), the bladder (39% at 60 keV) and the uterus (37% at 100 keV), especially when the simulator is irradiated in AP geometry. In this same irradiation geometry, the conversion coefficients E/Kair presented relative differences until 27% (at 10 keV), due to a change in absorbed dose of organs with relevant wT , which are located in the anterior portion of the simulator. Thus, the calculation of conversion coefficients HT / Kair and E/Kair using anthropomorphic simulators in different postures is important for more precisely estimating of individual dose in real scenarios of radiation exposure.